Fintech as a Precondition of Transformations in Global Financial Markets - Sergey Belozyorov; Olena Sokolovska; Young Sik Kim (Foresight and STI Governance)
The article considers opportunities, risk and challenges of development of digital financial technologies. To identify them we use the scenario approach. We determine three main development scenarios for the market of innovative financial technologies — “domination of traditional financial companies”, “segmentation of market of new financial technologies’, and “domination of digital financial companies”, in terms of their probability and possible consequences for the global financial markets. The results of analysis allowed to suggest that among main scenarios of FinTech development the most probable is the splitting of existing market, that in perspective can generate into the market of digital transnational financial corporations, which will squeeze out both small companies and traditional financial giants. However, although the scenario of capturing the financial market by big players is currently unlikely, but it is certainly more important in terms of the consequences for the global markets.The main prerequisite for the latest scenario is the promotion of international cooperation in the regulation of digital financial companies. Such a prerequisite requires new models of country-level interaction in regulation of innovative financial companies in order to address risks and challenges of different scenarios of FinTech development in global financial markets. The article includes comparative analysis of digital development in Russia and Republic of Korea, which is one of the key players on the Asian FinTech market, as a possible benchmark to shape policies of intergovernmental cooperation in the global financial markets. These policies include 1) a regulatory cooperation that reduces regulatory risks due to growing experience in regulation of innovative financial companies; 2) an investment cooperation allowing to acquire additional experience in regulatory practices and to develop infrastructure, which meets new requirements of digital finance; and 3) a cooperation on taxation of FinTech companies that reduces cross-border regulatory arbitrage.